The impact of carbon emission trading schemes on corporate green innovation - Cheng, Zhonghua; Wang, Lan (Journal of cleaner production, 2025)
The carbon emission trading scheme (CETS) facilitates efficacious resource allocation through the exchange of carbon emission quotas tailored to the specific needs of distinct entities. The growing significance of CETS in propelling corporate green innovation (GI) has emerged as a pivotal subject. Utilizing the double machine learning model to transcend the constraints of conventional approaches, this work assesses the influence and underlying mechanisms of CETS on GI, leveraging a dataset of Chinese listed firms spanning 2010 to 2022. The research findings reveal a positive correlation between corporate GI and CETS, with the CETS significantly fostering GI endeavors in corporate end governance. Mechanism testing corroborates that CETS augments corporate GI by heightening both internal and external pressures faced by corporates and providing incentives for them. Moreover, the innovation induced by this policy has displaced other innovation resources, manifesting a discernible crowding-out effect. Heterogeneity analysis highlights a stronger effect of CETS on GI within large-scale, private, environmentally conscientious corporates and corporates in the eastern region. •CETS can promote corporate green innovation.•CETS promotes corporate green innovation through pressure and incentive effects.•CETS promotes corporate green innovation based on the crowding out effect on other technological innovation resources.•CETS has mainly stimulated green innovation activities in the end of pipe governance of corporates.